The relevance of using methods of molecular epidemiology of HIV to characterize territorial epidemics: Sakhalin region, Russia - I. P. Osipova; A. V. Totmenin; P. G. Bersenev; E. Yu. Ilyina; E. A. Lomakina; N. M. Gashnikova; И. П. Осипова; А. В. Тотменин; П. Г. Берсенев; Е. Ю. Ильина; Е. А. Ломакина; Н. М. Гашникова (Mammal Review, 2023)
Aim. To investigate the molecular-epidemiological characteristics of the territorial distribution of HIV infection in the Sakhalin region.Materials and Methods. A comprehensive analysis of molecular-genetic characteristics of HIV-1 and clinical-epidemiological data of 64 HIV-infected residents of the Sakhalin region was conducted. Nucleotide sequences of the pol gene region encoding protease, reverse transcriptase, and integrase of HIV-1 were obtained by sequencing amplified virus fragments. Genotyping, phylogenetic and mutational analyses were performed using specialized software resources.Results. Among the HIV-1 cases studied, the HIV-1 subtype A6 was detected in 81.3 % of cases, with 58.4 % of them reliably clustering into closely related HIV groups, indicating the development of internal epidemic networks of infection transmission. Additionally, HIV-1 CRF63_02A6 and 06_cpx were detected in 4.7 % of cases each, subtype B and B/G in 3.1 %, subtypes C and A1 in 1.6 %. HIV-1 A6, B/G variants, and subtype A1 similar to Mediterranean HIV were detected in the MSM group. In 10.8 % of cases, treatment-naive patients had HIV-1 with the K103N mutation, and in one case, multiple drug resistance was identified.Conclusion. The contemporary territorial epidemic of HIV infection in the Sakhalin region is characterised by the presence of internal epidemic networks and the registration and spread of imported HIV. Key population groups with HIV infection require special attention due to the documented transmission of ART-resistant viruses. Studying the peculiarities of HIV infection spread in individual regions of Russia is important for the development of effective measures aimed at ending HIV transmission in the country. Цель. Исследовать молекулярно-эпидемиологические особенности территориального распространения ВИЧ-инфекции в Сахалинской области.Материалы и методы. Выполнен комплексный анализ молекулярно-генетических характеристик ВИЧ-1 и клинико-эпидемиологических данных 64 ВИЧ-инфицированных жителей Сахалинской ...